A Meta‐Analysis of Gamification's Impact on Student Motivation in K‐12 Education - Furkan Kurnaz, M.; Koçtürk, Nilüfer (Psychology in the schools, 2025)
Gamification is widely used to enhance student learning and engagement. This meta‐analysis focused on experimental research examining the effects of gamification on student motivation in K‐12. Studies were retrieved from Scopus, PubMed, Web of Science, and ProQuest, resulting in 279 articles screened, with 31 meeting the inclusion criteria. The pooled effect size ( k = 41) for gamification was g = 0.654 (95% CI [0.442, 0.866]) under a random effects model, with high heterogeneity observed ( I 2 = 88.92). Unlike previous meta‐analyses, this study simultaneously compared gamification's effects on intrinsic versus extrinsic motivation and analyzed grade‐level differences across primary, secondary, and high school students. Gamification had a greater impact on extrinsic motivation ( g = 0.713, 95% CI [0.152, 1.275]) than intrinsic motivation ( g = 0.638, 95% CI [0.239, 1.036]). Additionally, gamification was the most effective among secondary school students ( g = 1.015, 95% CI [0.639, 1.391]), followed by high school students ( g = 0.821, 95% CI [0.523, 1.119]) and primary school students ( g = 0.309, 95% CI [0.033, 0.584]). These findings provide developmentally tailored, practical insights for designing effective gamified learning environments. Gamification significantly enhances student motivation in K–12 education, particularly when game elements are aligned with students' developmental stages and learning needs. Extrinsic motivation benefits more strongly from gamification than intrinsic motivation, suggesting the importance of balancing reward‐based strategies with elements that foster curiosity and autonomy. Secondary school students show the greatest motivational gains from gamification, highlighting the need for age‐specific design when integrating gamified approaches into educational programs.